2010
DOI: 10.1542/peds.2010-2821
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Management of Eating Disorders in Children and Adolescents

Abstract: The incidence and prevalence of eating disorders in children and adolescents has increased significantly in recent decades, making it essential for pediatricians to consider these disorders in appropriate clinical settings, to evaluate patients suspected of having these disorders, and to manage (or refer) patients in whom eating disorders are diagnosed. This clinical report includes a discussion of diagnostic criteria and outlines the initial evaluation of the patient with disordered eating. Medical complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
176
0
18

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(194 citation statements)
references
References 140 publications
(166 reference statements)
0
176
0
18
Order By: Relevance
“…This aspect differs substantially from what have been observed among girls, who resort more frequently to induce vomiting and fasting periods, and therefore it should be considered when evaluating boys with ED 1,5 .…”
Section: Resultsmentioning
confidence: 73%
See 2 more Smart Citations
“…This aspect differs substantially from what have been observed among girls, who resort more frequently to induce vomiting and fasting periods, and therefore it should be considered when evaluating boys with ED 1,5 .…”
Section: Resultsmentioning
confidence: 73%
“…More recently, studies have found an increase in the frequency of ED among boys [3][4][5] . A study conducted in Australia with a sample of 101 children and adolescents treated in an ED program found that 25% (1:4) of the participants were boys 6 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…La distribución de riesgo entre mujeres y hombres que encontramos fue aproximadamente de 2/1, lo que no coincide con lo reportado en TCA en población no obesa, donde es mucho más frecuente en mujeres que hombres (10/1) 5 . Esta frecuencia por sexo es similar con lo observado en estudios de prevalencia de TCA en obesos, específicamente de trastorno por Atracón 24,33 .…”
Section: Discussionunclassified
“…Por otro lado, los adolescentes muestran un aumento de los trastornos de la conducta alimentaria (TCA) 4 . Ambas patologías constituyen problemas de salud pública complejos y prevalentes que requieren ser abordados [5][6][7][8][9] .…”
unclassified